The Food Safety Modernization Act of 2011: Final Rule for Preventive Controls for Human Food - Jessica Lepper; Soohyoun Ahn; Keith R. Schneider; Michelle Danyluk; Renée M. Goodrich Schneider (EDIS)
This 7-page fact sheet is one in a series covering the different rules promulgated under the new Food Safety Modernization Act (FSMA), which was signed into law on January 4, 2011. It is intended to provide an overview of the final Preventive Controls for Human Food (PCHF) rule. Written by Jessica A. Lepper, Soohyoun Ahn, Keith R. Schneider, Michelle D. Danyluk, and Renee Goodrich-Schneider and published by the UF/IFAS Department of Food Science and Human Nutrition, January 2018. http://edis.ifas.ufl.edu/fs301